Medical Tele-consultation in the Opinion of Patients of the Medical Entity in Poland in 2021 - Maria PŁONKA; Jolanta STANIENDA; Anna GĄDEK (Communications of International Proceedings, 2021)
Background: In March 2021, one year has passed since the COVID 19 pandemic appeared in Poland. The quantitative increase in telemedicine services, triggered out of necessity by a pandemic, does not necessarily indicate a qualitative development which is measured by satisfaction with tele-consultation. The aim of the study was to determine about patients' opinions on the quality of medical tele-consultation after a year of pandemic experience in Poland. In February and March 2021, five problems in five age cohorts from 18 - 80 years (N = 500) were examined using the Likert scale, using the following survey techniques: CAWI (N = 104), CATI (N = 31), PAPI ( N = 365). Results: In the opinion of all respondents, tele-consultation is not a better solution than a personal visit to a doctor. The quality of tele-consultation was assessed more negatively by specialist physicians than by general practitioners. The respondents did not have an unambiguous opinion regarding the comparison of the quality of tele-consultation with the quality of a personal visit to a doctor. At the same time, the respondents who used the tele-consultation were moderately satisfied with it. The sense of security of the patient's personal and medical data was also moderately positive. Conclusion: The respondents only show understanding for the current conditions. In the event of a pandemic, tele-consultation is a better solution than the risk of contracting a virus or the lack of advice in conditions of excessive workload of patient care facilities.
Keywords: COVID-19; pandemic; Healthcare system; telemedicine; e-health; tele-consultation.